MUTUAL RELATIONS OF THE CAUCASIAN COUNTRIES - ZABIL ALIYEVA, Ilaha (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
The paper provides a brief review of establishment and development of relations in Azerbaijan over the last 25 years. It describes the different phases of this development and how cooperative country has traditionally dealt with the benefits. The paper notes that to expand an effective cooperation the nations need to work on a particular field following various rules. The author mentions specific tips and groups of communication culture and etiquette that is very important to set up on a firm and evolve the mutual cooperation and relations between countries. The cooperation of individual states in a certain format in the Caucasus region, which is one of the most geopolitically vulnerable regions, can cause various reactions. If we take into account the fact that historically the Caucasus was in the focus of attention not only of regional forces but also of global forces, the expected backwardness of these reactions is expected. Therefore, it is important to emphasize the importance, first of all, of the political will for the trilateral cooperation of Azerbaijan, Georgia and Turkey. The basis of tripartite cooperation between Azerbaijan, Georgia and Turkey was built on the basis of economic interests and meets the national interests of all three countries. Since Azerbaijan is a source and producer of hydrocarbon resources, Georgia has a favorable geographical location and transit potential, Turkey has domestic energy demand and is a regional hub, all this is a natural basis for tripartite cooperation. The joint creation of economic and transport corridor makes this approach a historical necessity. Thus, the trilateral format of cooperation between Azerbaijan, Georgia and Turkey can be called a successful model, which can serve to build sustainable peace and progress in the Caucasus.